DESINFECTION SOCIALIZATION OF MAKING DENTURES FOR AVOIDING CROSS INFECTION IN DENTAL ARTISANS AT KECAMATAN SAMBENG, LAMONGAN CITY - Endang Kusdarjanti; Okti Setyowati; Sujati Sujati (Darmabakti Cendekia: Journal of Community Service and Engagements, 2021)
Background: Since time immemorial the existence of dental artisans has been neglected, even though many members of the community are involved as consumers of existing dental artisans. The dental artisans at Resik Village, Sambeng sub-district, Lamongan City do not yet know the dangers of cross infection when making dentures and how to do to prevent it. Objective: This activity aims to increase the awareness of dental artisans to avoid cross-infection between dental artisans and consumers. Method: This activity for the Resik Village community was carried out in the form of socialization to dental artisan partners, demonstrations on how to use disinfectant materials to dental artisans, as well as evaluation and monitoring of programs in the field. Results: This activity program was attended by 40 dental artisan participants where only 10 participants participated face-to-face due to the Covid 19 pandemic. Thirty other participants were given a video socialization of the activity. Disinfection socialization activities were carried out in 2 ways, namely disinfection by immersing teeth in a disinfectant solution and by dipping the teeth in a disinfectant solution. spray method. Conclusion: The participants gained additional knowledge about cross-infection, the consequences of these infections, and how to carry out disinfection when making dentures.